Mobility and Upright Posture Are Associated with Different Aspects of Cognition in Older Adults - Cohen, Rajal G.; Vasavada, Anita N.; Wiest, Michelle M.; Schmitter-Edgecombe, Maureen (Frontiers in Aging Neuroscience, 2016)
Objectives: Aging is associated with cognitive decline, including visuomotor and memory concerns, and with motor system changes, including gait slowing and stooped posture. We investigated the associations of visuomotor performance and episodic memory with motor system characteristics in healthy older adults. Methods: Neurologically healthy older adults (N=160, aged 50-89) completed a battery of cognitive and motor tasks. Cognitive variables were grouped by principal components analysis into two components: visuomotor performance and verbal episodic memory. Our primary predictor variables were two aspects of motor function: timed-up-and-go (TUG) speed and neck angle. Additional predictor variables included demographic factors (age, sex, and education) and indicators of physical fitness (body mass index and grip strength). All seven predictor variables were entered stepwise into a multiple regression model for each cognitive component. Results: Poor visuomotor performance was best predicted by a combination of advanced age, high BMI, and slow TUG, whereas poor verbal memory performance was best predicted by a combination of advanced age, male sex, low education, and acute neck angle. Discussion: Upright posture and mobility were associated with different cognitive processes, suggesting different underlying neural mechanisms. These results provide the first evidence for a link between postural alignment and cognitive functioning in healthy older adults. Possible causal relationships are discussed.